An anthropological approach to the concept of social construction Among the early social anthropological thinkers (Racliffe Brown-Malinowski-Evans-Pritchard) - خرما ايفا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research aims, first and last, to provide a methodological/anthropological statement on the concept of social construction in the thought of the early anthropologists (Racliffe Brown, Malinowski, Evans-Pritchard), in light of explaining the meaning of the concept of social construction according to them, their additions, and the new implications they brought about this concept Then employ this analytical approach to explain the intellectual concepts that are related to the concept of social structure, as they expressed it..